Thermal, optical and structural properties of Tb doped zinc aluminum phosphate glasses. Issue 1 (January 2015) - Yung, S.W.; Chiang, H.Y.; Lai, Y.S.; Wu, F.B.; Fu, Chuni; Lee, Yi-Mu
Abstract: Zinc aluminum phosphate (ZAP) glasses and Tb 3+ ions doped zinc aluminum phosphate (Tb doped ZAP) glasses have been prepared by melt quenching method. The effects of the ZnO and Tb2 O3 content on the thermal, optical and structural properties of the ZAP, (90− x ) P2 O5 –10Al2 O3 – x ZnO ( x =30, 35, 40 mol%), and the Tb doped ZAP, (90− x )ZAP x Tb2 O3, vitreous systems were investigated. It was found that the glass transition temperature ( T g ) and glass dilatometric softening temperature ( T d ) were lowered as ZnO content increased. The addition of Tb 3+ ions also increases the T g and T d, and the coefficient of thermal expansion (CTE) is reduced to less than 5×10 −6 /°C under higher Tb2 O3 content. Higher refractive index ( n ~1.55) is achieved for Tb doped ZAP under higher ZnO and Tb2 O3 content. Besides, the Tb doped ZAP shows greater chemical durability with the dissolution rate as low as 3×10 −7  g/cm 2 -min. Analyses from FTIR, Raman and NMR spectroscopies are discussed in comparison with the quantitative results of bridging oxygen (BO) and non-bridging oxygen (NBO) by O1s-XPS. It was found that the metaphosphate (Q 2 ) dominates the ZAP glasses; however, the pyrophosphate (Q 1 ) becomes significant for the Tb doped ZAP under addition of higher Tb2 O3 content, leading the enhanced glass network. Highest Tb 3+ /Tb 4+ ratio with value of 2.33 is observed for (90− x )(50P2 O5 –10Al2 O3 –40ZnO)– x Tb2 O3 ( x =3), which exhibits much enhanced emission band at 545 nm. Also, the sensitized effect of ZnO on the emission band is verified. The enhanced emission properties suggest that the Tb doped ZAP glass is a promising material for the application in green LED device by modulation of Tb composition.